MMS Observations of Double Mid-Latitude Reconnection Ion Beams in the Early Non-Linear Phase of the Kelvin-Helmholtz Instability - Eriksson, Stefan; Ma, Xuanye; Burch, James L.; Otto, Antonius; Elkington, Scot; Delamere, Peter A. (Frontiers in Astronomy and Space Sciences, 2021)
The MMS satellites encountered a Kelvin-Helmholtz instability (KHI) period in the early non-linear phase at the post-noon flank magnetopause on 8 Sep 2015. The adjacent magnetosheath was characterized by a pre-dominantly northward Bz>0 magnetic field with weakly positive in-plane components in a GSM coordinate system. Ion velocity distribution functions indicate at least 17 KH vortex intervals with two typically D-shaped ion beam distributions, commonly associated with reconnection exhausts, that stream in both directions along a mostly northward magnetic field at 350-775 km/s with a median 525 km/s ion beam speed. The counter-streaming ion beams are superposed on a core population of slowly drifting magnetosheath ions with a field-aligned 50-200 km/s speed. Each interval lasted no more than 5.25 s with a median duration of 1.95 s corresponding to in-plane spatial scales 3 < ΔS < 22 di assuming a constant 1 di=61 km ion inertial scale and a tailward VKH~258 km/s KH vortex propagation speed along the MMS trajectory. The counter-streaming ions are predominantly observed in the warm KH vortex region between the cold magnetosheath proper and the hot isotropic ion temperature of a low-latitude boundary layer as the MMS constellation traverses a KH vortex. The in-plane spatial scales and the locations of the observed counter-streaming ion beams generally agree with the predictions of twice-reconnected magnetic fields at two mid-latitude reconnection (MLR) regions in a two-fluid three-dimensional numerical simulation previously reported for this KH event. MMS typically recorded a higher phase space density of the fast parallel ion beam that we associate with a tailward reconnection exhaust from the southern MLR (SMLR) and a lower phase space density of the fast anti-parallel ion beam that we associate with a tailward reconnection exhaust from the northern MLR (NMLR) of similar speed. This is either consistent with MMS being closer to the SMLR region than the NMLR region, or that the KHI conditions may have favored reconnection in the SMLR region for the observed in-plane magnetosheath magnetic field as predicted by a two-fluid three-dimensional numerical simulation.